The inhibitory effect of extracts of elm and eucalyptus and the synergy between its active ingredients and antibiotics in Staphylococcus aureus and Salmonella typhimurium isolated from food poisoning - Fatema AL-Dulaimi; Khuder Suliman (College of Education for Pure Sciences, 2008)
SUMMARY In this study, Staphylococcus aureus and Salmonella typhimurium were isolated and identified from patients suffering from food poisoning, (250) samples showed positive bacterial growth (96.1%). After the biochemical tests were done, (60) isolates (41.4%) showed Staph. aureus and (85) isolates (58.6%) showed S. typhimurium. After detecting the inhibitors effect of plant extracts and active components on the bacteria under study, the aqueous, ethanolic, chloroform and acetone extracts of Slippery elm bark have also good inhibitory effects against Staph. aureus while then benzene extract is not effective. The aqueous, ethanolic and acetone extracts have clearly inhibitory effects on S. typhimurium. The isolated phenolic acid compounds from Slippery elm have highly inhibitory effect against Staph. aureus while they are less effective against S. typhimurium. The eucalyptus leaves extracts and the isolated essential oils showed to be good inhibitors against Staph. aureus while S. typhimurium is not affected. The minimum inhibitory concentration (MIC) of plant extracts under study and the separated active components were also identified. In addition, the antibiotic sensitivity of both types of bacteria with the presence of the active components was also tested. The results showed that active components have synergistic effect against Staph. aureus but antagonistic effect against S. typhimurium.